Ocena wybranych procedur analizy skupień dla danych porządkowych - Walesiak, Marek; Dudek, Andrzej (Finding Groups in Ordinal Data - an Examination of Some Clustering Procedures, 2009)
The major steps in a cluster analysis procedure for ordinal data contain: selection of objects and variables, selection of a distance measure, selection of clustering method, determining the number of clusters, cluster validation, describing and profiling clusters. In the article, based on data simulated with cluster.Gen function of clusterSim package working in R environment, some cluster analysis procedures containing GDM distance for ordinal data, nine clustering methods and eight internal cluster quality indices are evaluated. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 41-49